Development and Evaluation of Tractor Operated Belt Type Cotton Planter - Kamaraj, P; Kathirvel, K (Journal of Agricultural Engineering, 2008)
Cotton plays a major role in Indian economy and offers employment for more than 60 million people. Cotton planting is conventionally done by manual dibbling which involves maximum manual labours compared to the other operations, ultimately resulting in higher cost of cultivation. The cotton planting needs to reduce the operational costs, minimizing human drudgery and increase the production. The appropriate crop, machine and operational parameters were identified and a tractor operated prototype belt type cotton planter was developed and evaluated for its performance in actual field conditions. The performance of belt type cotton planter was compared with pneumatic planter, ridger seeder and manual planting. The belt type cotton planter recorded minimum draft of 950 N and minimum fuel consumption of 3.79 Ih?Â¹ . The belt type cotton planter proved its superiority by registering 73.33% of two plants per hill, 6.67% of missing hills and maintained the recommended plant population and desired plant spacing. The use of belt type cotton planter for planting cotton resulted in 68.62 and 98.46% saving in cost and time, respectively when compared to the manual planting.